1995
DOI: 10.1111/j.1432-1033.1995.1053g.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin‐B12‐Independent Methionine Synthase from a Higher Plant (Catharanthus Roseus)

Abstract: Methionine synthases catalyze the formation of methionine by the transfer of a methyl group from 5‐methyltetrahydrofolate to homocysteine. This reaction is the last step in l‐methionine biosynthesis, and it also serves to regenerate the methyl group of 5‐adenosylmethionine, a cofactor required for biological methylation reactions. We describe the cloning, expression and characterization of a methionine synthase from the higher plant Catharanthus roseus. cDNAs were identified that encoded a protein of 85 kDa sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…In prokaryotes, there are over 20 enzymes that have a cobalamin cofactor (Marsh, 1999), while in animals there are just two B 12 ‐dependent enzymes, methylmalonyl‐CoA mutase, involved in odd‐chain‐fatty‐acid metabolism in the mitochondria, and methionine synthase (METH), which catalyses the C1 transfer from methylhydrofolate to homocysteine to make methionine (Drummond et al ., 1993). Vitamin B 12 is not found in, or required by, land plants or fungi, because they contain no cobalamin‐dependent enzymes (Eichel et al ., 1995), and instead encode a B 12 ‐independent form of methionine synthase (METE). In contrast, the vitamin is widespread throughout the algal kingdom, and algae such as the seaweed Porphyra yezoensis (nori), are an extremely rich dietary source of cobalamin (Watanabe et al .…”
Section: Introductionmentioning
confidence: 99%
“…In prokaryotes, there are over 20 enzymes that have a cobalamin cofactor (Marsh, 1999), while in animals there are just two B 12 ‐dependent enzymes, methylmalonyl‐CoA mutase, involved in odd‐chain‐fatty‐acid metabolism in the mitochondria, and methionine synthase (METH), which catalyses the C1 transfer from methylhydrofolate to homocysteine to make methionine (Drummond et al ., 1993). Vitamin B 12 is not found in, or required by, land plants or fungi, because they contain no cobalamin‐dependent enzymes (Eichel et al ., 1995), and instead encode a B 12 ‐independent form of methionine synthase (METE). In contrast, the vitamin is widespread throughout the algal kingdom, and algae such as the seaweed Porphyra yezoensis (nori), are an extremely rich dietary source of cobalamin (Watanabe et al .…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes are required for the regeneration of the methyl group of S-adenosyl-Lmethionine, a methyl donor for several biological methylation reactions (Eichel et al 1995). Expression of microspores specific WRKY34 was enhanced by more than 2-fold in treated plant samples.…”
Section: Functional Categories Of the Identified Proteins And Their Rolementioning
confidence: 96%
“…Initially, it had been thought that the synthesis of Met required homocysteine to be transported from plastids to the cytoplasm, as there was no evidence of a Met synthase enzyme in the plastids (Eichel et al, 1995). However, following the identification of plastid-localized Met synthase, it was concluded that plastids are indeed capable of de novo synthesis of Met (Ravanel et al, 2004), and so a pool of Met could be sequestered within plastids that is not available for synthesis of aliphatic GSLs ( Figure 5 ).…”
Section: Transport Of Inorganic and Organic Smentioning
confidence: 99%